KENAIKAN ANGGARAN MILITER DALAM KONTEKS KEMANUSIAAN MODERN FACE IN HUMANITARIAN WORLD - Itsnaini Yusuf, Rifqi (Penerbit CV Tentrem Karya Nusa, 2019)
Abstract: This article aims to analyze the development of the increase in the country's militarybudget in the context of humanity and see it in a modern face of humanitarian world perspective.This article argues that there is a significant influence from the increase in the state's militarybudget on existing humanitarian issues. The increase in a country's military budget has at least twoimpacts, namely domestic and international impacts. Improving regional security and stability inthe domestic context is one of the effects of an increase in a country's military budget. neighboringcountries concerns over an increase in a country's budget reflects the adverse impact of theincrease in the budget. The existence of these concerns will actually raise the tension of relationsbetween countries that are in conflict. The conflict resulting from the increase in tension that isbuilt will threaten existing humanitarian aspectsKey Words: Military, State, Humanitarian, Stability, Security